Optimizing the efficiency of gallium nitride-based lightemitting diodes from contact area of current spreading to electrode - Shaari, Adam; Ahmad Fajri, Faris Azim; Ahmad Noorden, Ahmad Fakhrurrazi; Abdul Kadir@Jaafar, Muhammad Zamzuri; Daud, Suzairi (1098-2760, 2020)
A nonuniform current spreading in the current spreader layer greatly reduced the internal quantum efficiency (IQE) of the light-emitting diodes (LED). The effects of the current spreading layer on the electrode contact area toward the IQE in a vertical design of gallium nitride (GaN)-based LED chip is analytically analyzed. The contact area was varied by changing the value of the electrode’s width from 2 to 12 μm. Efficiency droop and current density at peak IQE are analyzed based on contact area. The width of 2 μm requires 1.6 μAm−2 current density to achieve peak efficiency and produces a droop of 0.2150. The width of 12 μm requires 9.6 μAm−2 current density to achieve peak efficiency and produces 0.0557 droop. The increase in contact area increases the current A nonuniform current spreading in the current spreader layer greatly reduced the internal quantum efficiency (IQE) of the light-emitting diodes (LED). The effects of the current spreading layer on the electrode contact area toward the IQE in a vertical design of gallium nitride (GaN)-based LED chip is analytically analyzed. The contact area was varied by changing the value of the electrode’s width from 2 to 12 μm. Efficiency droop and current density at peak IQE are analyzed based on contact area. The width of 2 μm requires 1.6 μAm−2 current density to achieve peak efficiency and produces a droop of 0.2150. The width of 12 μm requires 9.6 μAm−2 current density to achieve peak efficiency and produces 0.0557 droop. The increase in contact area increases the current